" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
b). (2+x)³+2(x-1)³=8+12x+6x²+x³+2(x³-3x²+3x-1)=8+12x+6x²+x³+2x³-6x²+6x-2=
=3x³+18x+6
c). (x+1)(x²-x+1)+(1-x)³=x³+1³+x³-3x²+3x-1=2x³-3x²+3x
d). 3(x-2)(x²+2x+4)-(x+3)³=3(x³-2³)-(x³+9x²+27x+27)=3x³-24-x³-9x²-27x-27=
=2x³-9x²-27x-51
e). (x+4)³-(4-x)(x²+4x+16)=x³+12x²+48x+64-(4³-x³)=x³+12x²+48x+64-64+x³=
=2x³+12x²+48x
f). (∛5+x)³-(∛5-x)³-6∛25x=5+3∛25x+3∛5x²+x³-5+3∛25x-3∛5x²+x³-6∛25x=
=2x³